(untitled) (Al-Academy, 2016)
The research is a special case of semantics modern Iraqi art, especially with regard to the art of sculpture, and the exact Nasba sculpture, has included research, four chapters on whale1. The first chapter: which consisted of:A. The research problem.B. The importance of research.C. Find goal.H. Find borders.Kh. Determine the terms.2. Chapter II: The theoretical framework: which consisted ofA. The first topic: sculptured configuration.B. The second topic:1. The first axis: contemporary Iraqi sculpture.2. The second axis: the sculptor Jawad Salim.3. The third axis: Mohammed sculptor debateC. Theoretical framework indicators.D. Previous studies.3. Chapter III: proceedings: which included:A. Find community.B. The research sample.C. Research Methodology.D. Analysis of the sample.4. Chapter IV: which encompassedA. Results: It is the most importantParticipants and points of convergence and similarities between Nasben:1. Are both works of several training Haddah represent work as a single Nsbah unit.2. Use both Alnhatan, several sculptural styles in implementation of configurations vocabulary work.3. Using the style of the wall, or the sign to promote the missionary dimension.4. Borrow the style of the Sumerian cylinder seal imprint.5. Penetrate the dimension of time, for the sustainability of events.6. The use of texture and color, in the service of shape, and increase Bjamalith.7. Use of space, and the level of consideration, to enhance the aesthetic configurations.8. Borrowed symbols associated with the lives and rights of the Iraqi entity, increased aesthetic value and vitality in configurations Nasben.Points of intersection and difference:1. Used in the Freedom Monument bronze, while Class fiber material used in the monument Eid al-Ghadir.2. Use sculptor shapes expressive and realistic manner in the Freedom Monument, while sculptor formats used abstract manner symbolic monument Eid al-Ghadir.3. Aesthetic discourse configurations Freedom Monument holds the contents of a. liberal intellectual, and aesthetic discourse in the monument Eid Ghadir epistolary religious ideal B. Recommendations.C. Proposals.5. Supplements that whale:A. Margins.B. Sources.